Computed tomography assessment of lung structure in patients undergoing cardiac surgery with cardiopulmonary bypass - Rodrigues,R.R. (2011)
Hypoxemia is a frequent complication after coronary artery bypass graft (CABG) with cardiopulmonary bypass (CPB), usually attributed to atelectasis. Using computed tomography (CT), we investigated postoperative pulmonary alterations and their impact on blood oxygenation. Eighteen non-hypoxemic patients (15 men and 3 women) with normal cardiac function scheduled for CABG under CPB were studied. Hemodynamic measurements and blood samples were obtained before surgery, after intubation, after CPB, at admission to the intensive care unit, and 12, 24, and 48 h after surgery. Pre- and postoperative volumetric thoracic CT scans were acquired under apnea conditions after a spontaneous expiration. Data were analyzed by the paired Student t-test and one-way repeated measures analysis of variance. Mean age was 63 ± 9 years. The PaO2/FiO2 ratio was significantly reduced after anesthesia induction, reaching its nadir after CPB and partially improving 12 h after surgery. Compared to preoperative CT, there was a 31% postoperative reduction in pulmonary gas volume (P < 0.001) while tissue volume increased by 19% (P < 0.001). Non-aerated lung increased by 253 ± 97 g (P < 0.001), from 3 to 27%, after surgery and poorly aerated lung by 72 ± 68 g (P < 0.001), from 24 to 27%, while normally aerated lung was reduced by 147 ± 119 g (P < 0.001), from 72 to 46%. No correlations (Pearson) were observed between PaO2/FiO2 ratio or shunt fraction at 24 h postoperatively and postoperative lung alterations. The data show that lung structure is profoundly modified after CABG with CPB. Taken together, multiple changes occurring in the lungs contribute to postoperative hypoxemia rather than atelectasis alone.